Perancangan Ulang Visual Brand identity Kedai Kue 99 - Shiddiq Hafizhulmalik; Adi Prehanto; Muhammad Dzikri Ar Ridlo (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study is motivated by the inconsistency of the visual identity of Kedai Kue 99, which has resulted in an underdeveloped brand image. This issue is commonly found among Micro, Small, and Medium Enterprises (MSMEs), particularly in building differentiation and effective visual communication. The purpose of this study is to redesign the visual brand identity of Kedai Kue 99 to be more consistent, representative, and capable of strengthening its market position. The research employs a qualitative approach with a case study method and refers to the brand identity design model by Wheeler (2013), which includes the stages of conducting research, clarifying strategy, designing identity, creating touchpoints, and managing assets. The results indicate that the redesign process produced a visual identity concept with the big idea “Preserving Taste, Reviving the Warmth of Nusantara Stories,” which is reflected in more consistent logo, color, and typography elements. Additionally, a Graphic Standard Manual was developed as a guideline for implementing the visual identity across various communication media. The conclusion of this study shows that the visual identity redesign enhances consistency, strengthens brand image, and supports the competitiveness of Kedai Kue 99 as a culture-based culinary MSME